Evaluation of the reality of the whistleblowing system on the quality of internal auditing: a case study in the General Company of Ur (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims primarily to study the evaluation of the reality of the whistleblowing system on the quality of internal auditing in Ur General Company. The research problem revolves around "How does the evaluation of the reality of the whistleblowing system contribute to the quality of internal auditing in Ur General Company?" The research was based on the hypothesis that "there is a positive contribution in evaluating the reality of the whistleblowing system on the quality of internal auditing in Ur General Company." The researcher relied on the descriptive analytical approach, where he designed a checklist for each of the whistleblowing system, consisting of 7 items, and containing 24 indicators, and the quality of internal audit, consisting of 7 items and containing 14 indicators targeting managers and department heads in Ur General Company, with a sample size of 60 individuals. The average method was used to extract the percentages. The research concluded with a set of conclusions, including that the system of reporting violations contributes to enhancing confidence in the integrity and transparency of the internal audit process, which encourages employees to cooperate with internal auditors, and that the existence of an effective system for reporting violations contributes significantly to improving the quality of internal audit, as it helps in detecting violations and problems early. The research came out with a set of recommendations, the most prominent of which is emphasizing the need to conduct a periodic evaluation of the whistleblowing system to ensure the continuity of its effectiveness and suitability to the changing needs of the company and to submit periodic reports on its effectiveness and its impact on the quality of internal audit.